2017
DOI: 10.1590/0034-7167-2016-0486
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal cuff pressure change before and after the performance of nursing care

Abstract: Objective: Verify the changes of endotracheal cuff pressure before and after oral hygiene, head-of-bed elevation at 0°, 30°, and 60°, change in body position, aspiration of the endotracheal tube, and in-bed bathing. Method: The study sample was composed of 88 patients. We performed 3,696 checks from July to September 2014. Results: Pressure values were analyzed in seven nursing care in the morning. Six of them were significantly altered before and after nursing procedure. In the afternoon, five of the health c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Kumar et al and Bulamba et al [ 189 , 190 ] proposed a pressure target of an ETT cuff at 20–30 cm H 2 O. The correct endotracheal cuff pressure must be less than the capillary perfusion pressure or less than 30 cm H 2 O [ 191 ]. Talekar et al [ 192 ] also suggested ETT cuff daily monitoring every 6–12 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Kumar et al and Bulamba et al [ 189 , 190 ] proposed a pressure target of an ETT cuff at 20–30 cm H 2 O. The correct endotracheal cuff pressure must be less than the capillary perfusion pressure or less than 30 cm H 2 O [ 191 ]. Talekar et al [ 192 ] also suggested ETT cuff daily monitoring every 6–12 hours.…”
Section: Discussionmentioning
confidence: 99%
“…National guidelines recommend that cuff pressure be maintained between 20 and 30 cm H 2 O for air-filled cuffs, to avoid loss of tidal volume and prevent tracheal injury. [113][114][115] Hyperinflation of cuffs to avoid any air leak is not uncommon in patients who are COVID-19 positive but incurs risk Water cuffs are commonly used in pediatric otolaryngology patients. These are high-pressure, low-volume cuffs for which pressure cannot be monitored with a manometer.…”
Section: Cuff Managementmentioning
confidence: 99%
“…It can be obtained from either tracheal aspirate, Broncho-alveolar Lavage (BAL), Mini-BAL or Protected Brush Specimens (PBS), each having sensitivity and specificity. (Beccaria et al, 2017) Positioning of the endotracheal tube is usually the responsibility of the physician, but in the intensive care units, nurses are overwhelmed to care for the endotracheal tube that will include the management of secretions, maintaining the position of the endotracheal tube, ensuring correct cuff pressures, prevention of complications and managing complications when they do occur after consulting the responsible physician. (Wen et al, 2019) The intensive care nurse has always been occupied with the prevention of ventilator-associated pneumonia.…”
Section: (Green Et Al 2017)mentioning
confidence: 99%